Strain Rate Dependent Ductile-to-Brittle Transition of Graphite Platelet Reinforced Vinyl Ester Nanocomposites - Brahmananda Pramanik; P. Raju Mantena (Advances in Materials Science and Engineering)
In previous research, the fractal dimensions of fractured surfaces of vinyl ester based nanocomposites were estimated applying classical method on 3D digital microscopic images. The fracture energy and fracture toughness were obtained from fractal dimensions. A noteworthy observation, the strain rate dependent ductile-to-brittle transition of vinyl ester based nanocomposites, is reinvestigated in the current study. The candidate materials of xGnP (exfoliated graphite nanoplatelets) reinforced and with additional CTBN (Carboxyl Terminated Butadiene Nitrile) toughened vinyl ester based nanocomposites that are subjected to both quasi-static and high strain rate indirect tensile load using the traditional Brazilian test method. High-strain rate indirect tensile testing is performed with a modified Split-Hopkinson Pressure Bar (SHPB). Pristine vinyl ester shows ductile deformation under quasi-static loading and brittle failure when subjected to high-strain rate loading. This observation reconfirms the previous research findings on strain rate dependent ductile-to-brittle transition of this material system. Investigation of both quasi-static and dynamic indirect tensile test responses show the strain rate effect on the tensile strength and energy absorbing capacity of the candidate materials. Contribution of nanoreinforcement to the tensile properties is reported in this paper.